Over 21.0% faradaic efficiency of ambient ammonia production: Photoelectrocatalytic activity of MOF-235 - Camargo, Luan Pereira (2022)
In recent years, the Haber-Bosh process's ammonia synthesis has shown a lot of energy consumption and significant CO2 emissions. In this sense, the photoelectrochemical production of NH3 via dinitrogen fixation has been showing a promising strategy. Thus, in this work, ammonia production under photoelectrocatalytic condition was carried out using the metal-organic iron terephthalate structure (MOF-235), obtained by a simple and low-cost process (solvothermal). The results indicated greater activity for the nitrogen reduction reaction (NRR) compared to the hydrogen reduction reaction (HRR), in addition to a high yield of NH3 0.716 µg h−1 cm−2 and Faradaic efficiency greater than 21.0% at - 0.2 V vs reversible hydrogen electrode in 0.1 mol L−1 Na2SO4 electrolyte. It is believed that the good results of MOF-235 during NRR are related to a high specific area of MOF, making available active sites of trinuclear-oxocentered iron in abundance. The material homogeneity in the electrode and the excellent light absorption were also decisive factors for the supply of high energy electrons necessary for ammonia production.